Moving Towards Society 5.0: A Bibliometric and Visualization Analysis - Shahidan, Noor Hidayah; Latiff, Ahmad Shaharudin Abdul; Wahab, Sazali Abdul (Society 5. 0, 2021)
This paper aims to provide a holistic approach for a brief understanding of the current state of literature of Society 5.0 by deciphering its characteristics, subjects, the geographical distribution of publications, keywords and general concepts by using bibliometric data retrieved from the Scopus database. We used descriptive analysis to examine publication characteristics, subjects and geographical distribution of published documents, Harzing’s Publish or Perish to calculate citation metric and VOSviewer version 1.6.16 for data and network visualization. Through the network analyses of author and index keyword co-occurrences, research clusters were revealed from different perspectives. The bibliometric analysis indicates that Society 5.0 is heavily influenced by the advancement of the Industrial Revolution (IR) 4.0. The intellectual structure of the Society 5.0 literature is being dominated by engineering-related fields, artificial intelligence (AI), and the Internet of Things (IoT). Our analysis revealed the existence of a strong link in the temporal co-map between Sustainable Development Goals (SDGs) and Society 5.0. This paper also emphasizes on university’s role as an important stakeholder in Society 5.0 ecosystem.